Structural Analysis of a Peptide (CTLTTKLYC) that Interacts with Newcastle Disease Virus - Chia, Suet Lin (2005)
A peptide with the sequence Cys-Thr-Leu-Thr-Thr-Lys-Leu-Tyr-Cys (CTLTTKLYC) has previously been identified to inhibit the propagation of Newcastle disease virus (NDV) in embryonated chicken eggs and tissue culture. It has two different dissociation constants (&"I), in which the first constant can be used as a determinant to classifjr NDV strains into two groups: the velogenic strains in the first group, whereas the mesogenic and lentogenic strains are in the second group. The peptide, C 1T 2L3 P T5K 6 L7 Y8 C9 ,d isplayed on the pIII protein of a filamentous M13 phage was mutated by oligonucleotide-directed mutagenesis in order to identify the amino acid residues involved in the interactions with NDV. Mutations of Cys at first position (c')a nd Lys at the sixth position of the peptide ( K ~t)o Ala (A), which produced mutants C'A and K~Ad,i d not affect the binding between the peptide and the virus significantly, but substitution of Tyr at eighth position (Y8) alone with Ala (A) dramatically reduced the interaction. This suggests that y8 couid play an important role in the peptide-virus interaction. Double mutations were carried out on K~ and y8 to produce mutants K~A-Y~AK,~ R-Y~AK,~ A-Y'F, and K ~ - Y ~ Fto, determine whether the mutated amino acids could improve the binding capability. However, the mutations did not improve the binding capability significantly. Fmoc-solid phase peptide synthesis was employed to synthesize the peptide, CTLTTKLYC. Crude peptide was purified with HPLC and analysed with a mass spectrometer. The secondary structure of the peptide was analysed with circular dichroism (CD) and the three dimensional conformation of the peptide was determined by nuclear magnetic resonance (NMR) and molecular modelling. A mixture conformation of p-turn and P-sheet (intermolecular interaction) was observed for the linear peptide by using CD. However, the three-dimensional structure of the linear peptide could not be arrived due to the mixture of conformation which made the sequence assignment of NMR extremely difficult. On the other hand, the disulfide-constrained cyclic peptide, which has a more rigid structure, exhibited only a P-turn structure. Two models were obtained: one of it consists of a p-turn and a distorted p-turn, while the other structure is an extended structure.